2021
DOI: 10.1186/s12968-020-00686-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory efficiency in patients with severe aortic valve stenosis before and after aortic valve replacement

Abstract: Background Circulatory efficiency reflects the ratio between total left ventricular work and the work required for maintaining cardiovascular circulation. The effect of severe aortic valve stenosis (AS) and aortic valve replacement (AVR) on left ventricular/circulatory mechanical power and efficiency is not yet fully understood. We aimed to quantify left ventricular (LV) efficiency in patients with severe AS before and after surgical AVR. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Another approach to evaluate global afterload in AS has been to explore the myocardial energy expenditure [ 36 ], which had been done using positron emission tomography to measure the myocardial oxygen consumption [ 37 , 38 ]. More recently, a CMR-based method had also demonstrated the calculation of myocardial energy consumption in AS [ 39 , 40 ]. However, both methods again fail to account for the pulsatile nature of the circulation, and each study found that TAVR failed to improve the myocardial efficiency of a proportion of patients in the medium term, which was defined as the ratio between steady-state circulatory energy consumption and the apparent myocardial energy consumption [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to evaluate global afterload in AS has been to explore the myocardial energy expenditure [ 36 ], which had been done using positron emission tomography to measure the myocardial oxygen consumption [ 37 , 38 ]. More recently, a CMR-based method had also demonstrated the calculation of myocardial energy consumption in AS [ 39 , 40 ]. However, both methods again fail to account for the pulsatile nature of the circulation, and each study found that TAVR failed to improve the myocardial efficiency of a proportion of patients in the medium term, which was defined as the ratio between steady-state circulatory energy consumption and the apparent myocardial energy consumption [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It could decrease significantly when the LV afterload was obviously elevated (27,28). Nowadays, non-invasive approaches independent of afterload were developed to identify myocardial dysfunction by investigating myocardial energetics and metabolism (29)(30)(31)(32). Unlike the myocardial power and power efficiency derived from cardiac magnetic resonance, which was partly based on wall stress analysis according to the Laplace law, non-invasive myocardial work indices measured with echocardiography come from the LV pressure-volume loop in principle.…”
Section: Discussionmentioning
confidence: 99%
“…All parameters were computed from cardiac magnetic resonance imaging-derived volumetric data and echocardiographic and clinical data. More details are described in former studies ( 14 ).…”
Section: Methodsmentioning
confidence: 99%